Do understanding nature of science (nos) play role to students understanding chemistry concept and science process skill? - Yusran Khery; Baiq Asma Nufida; S Suryati; Sri Rahayu; Endang Budiasih (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
The aim of this research was to evaluate how Understanding Nature of Science (NOS) play role to students Understanding chemistry concept and Science Process Skills on Chemistry Classroom. This descriptive research was carried out by Ex-post Facto method at the Faculty of Mathematics and Science Education of IKIP Mataram. The research subjects were 75 students participating in the General Chemistry course for the academic year 2018- 2019 that taken by the saturated sampling method. Data were collected by understanding of NOS questionnaire, Understanding chemistry concept Test, and Science Process Skills observation sheet. The data is described and analyzed by product moment correlation test and One Way Anova test for uncorrelated samples. The results showed that there was a significant and very strong correlation between Understanding of NOS and Understanding chemistry concept and between Understanding of NOS and Science Process Skills. One Way Anova test result showed that there was difference on Students Understanding chemistry concept and Science Processes Skills on different Understanding of NOS.